Unattended automated office blood pressure in living donor kidney transplant recipients - Minh Ngoc Nguyen; Karin Skov; Birgitte Bang Pedersen; Niels Henrik Buus (Blood Pressure, 2021)
Purpose Hypertension is common in kidney transplant recipients (KTRs). For the evaluation of blood pressure (BP), 24-h ambulatory BP measurements (ABPM) are considered superior to usual office measurements but are also resource demanding and troublesome to many patients. We therefore evaluated the use of unattended automated office BP (AOBP) during the first year following living donor kidney transplantation and compared AOBP with ABPM as obtained 12 months after transplantation. Materials and methods Data were retrieved from a cohort of 57 KTRs (mean age 45 ± 14 years, 75% males) who all received kidneys from living donors and had a good graft function (estimated glomerular filtration rate (eGFR) 52 ± 16 ml/min/1.73 m2 at 12 months). Unattended AOBP was measured at each visit to the outpatient clinic using the BpTru® device, while ABPM was obtained by Spacelabs® equipment before and 12 months after transplantation. Results AOBP remained stable from month 2 (130.2 ± 10.8/82.2 ± 7.8 mmHg) to month 12 (129.0 ± 12.8/83.1 ± 9.6 mmHg) post-transplantation. At 12 months follow-up, ambulatory daytime systolic BP was slightly higher than AOBP (132.7 ± 10.7 vs. 129.4 ± 12.2 mmHg, p = 0.04), while diastolic BP was similar (82.7 ± 7.7 vs. 82.0 ± 10.2 mmHg). Using Bland–Altman plots, 95% limits of agreements were −17.9 to 24.5 mmHg for systolic and −16.5 to 15.1 mmHg for diastolic BP. When considering a target BP of ≤130/<80 mmHg, 62% had sustained hypertension, 9% white coat hypertension and 11% masked hypertension. Using multiple linear regression analysis, only urine albumin-creatinine ratio tended to predict a higher systolic AOBP (p = 0.07). Conclusion In a cohort of stable living donor KTRs, mean values of unattended AOBP using BpTru® are comparable to daytime ABPM with a misclassification rate of approximately 20%.